Using Mastitis Records and Somatic Cell Count Data - Rhoda, David A.; Pantoja, José Carlos de Figueiredo [UNESP] (W B Saunders Co-elsevier Inc, 2012)
On-farm records are essential for managing mastitis in dairy herds. Mastitis records are a useful tool for caring for an individual cow, to monitor compliance of farm personnel working with groups of animals, to understand the epidemiology of mastitis in the herd, to ensure responsible drug utilization, and to document accountability in care of the cow. Herds have become larger and more people are involved with individual animal care. This article describes a records plan that can be used to monitor mastitis at the herd level, aid in decision-making processes for individual cows, and improve drug use on dairy herds.
Keywords: Mastitis; Milk quality; Records; Software